Czynniki determinujące wyznaczanie odległości pomiędzy drzewami zdefiniowanymi w języku XML - Lula, Peweł (The Determinants of the Distance Between XML Trees, 2007)
The issue of distance calculation between XML trees is the main subject of the; paper. Tree structures and their applications in XML technology were shown in the first part of the study. Some remarks on edit distance between trees and on two new algorithms of XML distance calculation are presented next. Finally the list of factors which determine the distance between trees is proposed and discussed. The analysis shows that the universal method of distance calculation does not exist and it is necessary to formulate the method of tree distance evaluation for each problem independently.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 297-304